PENINGKATAN HASIL BELAJAR PPKN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION PLUS DI MADRASAH IBTIDAIYAH - Suttrisno Suttrisno; Desy Nur Indah Prastiwi (SITTAH: Journal of Primary Education, 2023)
This study aims to increase civic education learning outcomes with the Student Teams Achievement Divisions (STAD) Plus learning model at Private Madrasah Ibtidaiyah. The study used the classroom action research procedure: planning, implementation, observation, and reflection. The results showed that the STAD Plus learning model could improve civic education learning outcomes. In the pre-cycle stage, the average student score was 75.46. In the first cycle, it was 86.27; in the second, it increased to 88. The positive response of students to the application of the STAD Plus type cooperative learning model reached an average rate of 97 percent.